Pengaruh Sapta Pesona, Citra Destinasi dan Promosi terhadap Niat Berkunjung Kembali pada Wisata BeeJay Bakau Resort Kota Probolinggo - Safarani, Elinda; Elmas, Muhammad Syarif Hidayatullah; -, Tumini (Ecobuss, 2024)
ABSTRACT This study aims to determine the effect of sapta pesona, destinatioin image and promotion partially and simultaneously on the intention to visit again on BeeJay Bakau Resort tourism in Probolinggo City. The research method used is quantitative with the independent variables of sapta pesona, destination image, promotion and the dependent variable is the intention to visit again. The population of this study were tourists who treveled to BeeJay Bakau Resortr Probolinggo City. The sampling technique was carried out on 120 respondents and the sampling technique used incidental sampling. The analysis stage begins with a validity test reliability test, classical assumption test, multiple linear regression anylis, determination coefficient test and hypothesis testing using SPSS version 26. The results showed that sapta pesona and destination image partially influenced the intention to visit again, while promotion had no partial effect in the intention to visit again, and there was a simultaneous influence between sapta pesona, destination image and promotion on the intention to visit again on the BeeJay Bakau Resort tour Probolinggoo City. Keywords : Sapta Pesona, Destination Image, Promotion, Revisit Intention